2013
DOI: 10.1186/1752-0509-7-s2-s9
|View full text |Cite
|
Sign up to set email alerts
|

Identifying novel glioma associated pathways based on systems biology level meta-analysis

Abstract: BackgroundWith recent advances in microarray technology, including genomics, proteomics, and metabolomics, it brings a great challenge for integrating this "-omics" data to analysis complex disease. Glioma is an extremely aggressive and lethal form of brain tumor, and thus the study of the molecule mechanism underlying glioma remains very important. To date, most studies focus on detecting the differentially expressed genes in glioma. However, the meta-analysis for pathway analysis based on multiple microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…TGF‐β can activate EMT in GBM via a Smad‐dependent and a Smad‐independent pathway . The most important of these, the Smad2/3 pathway, plays a predominant role in TGF‐β‐induced EMT in glioblastoma cell lines . Here, we have shown that Cy, Dp, Pg, and Pt attenuated TGF‐β‐induced phosphorylation of Smad2 in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 63%
“…TGF‐β can activate EMT in GBM via a Smad‐dependent and a Smad‐independent pathway . The most important of these, the Smad2/3 pathway, plays a predominant role in TGF‐β‐induced EMT in glioblastoma cell lines . Here, we have shown that Cy, Dp, Pg, and Pt attenuated TGF‐β‐induced phosphorylation of Smad2 in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 63%
“…Hundreds of gene expression profiles and diagnostic targets are uploaded into various gene expression databases. These data can be further integrated to the understanding of the complexity of the diseases, such as the cancer heterogeneity, high level consensus [ 11 13 ], biomarker discovery [ 14 , 15 ], and the key players in the cancer genesis and progress [ 16 ]. In this study, we used meta-analysis approach for analysis of multiple transcriptomic datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the abnormal expression of single genes may be better viewed collectively at the molecualr network level 18 . In addition, in contrast to single gene/protein targets for the treatment of glioma, these networks establish broader, multi-target pathways for glioma therapy 19 . In contrast to the entire transcription regulatory network, the subnetworks are formed by interactions among the TFs that are expressed in a given cell type, and these subnetworks make the cell system nimble and robust 20 .…”
mentioning
confidence: 99%